ENDOSCOPICALLY-ASSISTED MICROSURGICAL RESECTION OF FALCOTENTORIAL MENINGIOMA - Rojas, Hector Pablo (Revista Argentina de Neurocirugía, 2020)
Introduction: Meningiomas arising from the falcotentorial junction are extremely rare (constitute about 0.3-1.1 % of all intracranial meningiomas). To an appropriate surgical approach we must consider: (1) its position from the tentorium and falx, (2) dural venous sinuses system permeability, and (3) its relationship with the vein of Galen. The main aim of the surgery is the total resection of meningioma without compromising on the venous deep structures. Case: Our patient is a 63-year-old woman diagnosed with an extra-axial lesion at the falcotentorial junction in 2010. On the follow-up, a progressive growth of the meningioma have been shown by imaging studies, since the diagnosis. By year 2019, the patient had hydrocephalus for which was placed a VP shunt. Despite this procedure, our medical staff was required to get a second opinion and we achieved the accurate diagnosis as falcotentorial meningioma type II. We performed an endoscopically-assisted microsurgical resection of the tumor. Results: We achieved a near total resection, leaving only a small piece of tumor around the vein of Galen. Without showing any complications, the patient was discharged in the fifth postoperative day. Conclusion: Choosing the right approach is drastic on finding the most effective results. The microsurgical technique is the `gold standard’. The endoscopic technique is more comfortable to the position of our arms and enhances our vision where the microscope faces difficulties. We considered both techniques as complimentary for these types of procedures.